2022
DOI: 10.3389/fenvs.2022.946226
|View full text |Cite
|
Sign up to set email alerts
|

The Statistical Characteristics of Atmospheric Ducts Observed Over Stations in Different Regions of American Mainland Based on High-Resolution GPS Radiosonde Soundings

Abstract: Atmospheric duct is an anomalous atmospheric structure that affects electromagnetic wave propagation. The important characteristics of the atmospheric ducts include duct probability, duct height, duct strength, and the thickness of the trapping layer. To investigate the statistical characteristics of atmospheric ducts over the American mainland, four stations in different regions are chosen. The seasonal and diurnal variation of the characteristics of ducts is presented. The mechanism of the seasonal and varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…In addition, Huang et al. (2022) have observed that the thickness shows similar regularity with the duct height. Base and Top may process similar distributions, and they have height differences simultaneously, as Figure 4 shows.…”
Section: Proposed Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…In addition, Huang et al. (2022) have observed that the thickness shows similar regularity with the duct height. Base and Top may process similar distributions, and they have height differences simultaneously, as Figure 4 shows.…”
Section: Proposed Methodsmentioning
confidence: 87%
“…The EleD also creates an electromagnetic blind zone above the atmospheric duct, which harms the identification of air targets (Han et al., 2022). The height is one of EleD's characteristics (Huang et al., 2022). Elevated duct height (EleDH) is related to the local refractive index.…”
Section: Introductionmentioning
confidence: 99%